KOMBINASI PIJAT WOOLWICH DAN OKSITOSIN TERHADAP PRODUKSI ASI IBU POST PARTUM - ,, kusumastuti; laelatul Qomar, umi; Mutoharoh, Siti (Jurnal Ilmiah Kesehatan, 2019)
Abstract: Lactation is the whole breastfeeding process from breastmilk produced to the baby's process of sucking and swallowing milk. The process of lactation is strongly influenced by the hormone prolactin and oxytocin. Expulsion of prolactin and oxytocin hormones can be stimulated by massage one of them with woolwich massage and oxytocin massage. Determine the effect of combination of Woolwich and oxytocin massages on breast milk production of postpartum mother. Thepresent study used quasi non-equivalent control group design experiment with data analysis using chi-square. The study revealed the differences of breast milk production of the Woolwich massage group and the oxytocin massage compared to the control group. The subjects were0-7 days post-partum mothers who breastfed their baby exclusively, amounting to 22 respondents in each group. Variables of breast milk production, the combination of Woolwich and oxytocin massage have p-value of  higher than 0.05 so it is not statistically significant but clinically it showed that the breast milk production of intervention group had 17% higher than the control group. Although there was no significant effect of the combination of Woolwich and oxytocin massage on breast milk production but there was clinically differenceof outcomes that is visible in intervention groups.